A COMPREHENSIBLE NEED OF ZINC OXIDE VARISTORS IN ELECTRONICS TECHNOLOGY - Mahmood, F. S.; Nadeem, M.Y.; Jamail, U. (Journal of Research (Science), 2007)
A range of varistors, in terms of break down voltage, is required to protect integrated circuits, automotive systems and other modern electronics against transient over-voltages. There is a progressing need for the development and advancement of rugged and reliable varistor capable and proficient of working in harsh and callous environment like automotive industry where greater than before use of electronics technology has led to improvements in equipment performance and presentation. There is a comprehensible need to combine triumphant and succesable models developed at different length scales into an integrated framework that can be used to drive new research and guide experimental efforts and device development. The review of ZnO varistor in particular and metal-oxide varistors (MOVs) in general is presented in this article.